PERAN PEREMPUAN ANGGOTA KELOMPOK KEBUN DALAM PENINGKATAN EKONOMI KELUARGA PADA KEGIATAN URBAN FARMING (Studi Kasus di Kelompok Kebun Flamboyan) - Hanna Alynda; Rani Andriani Budi Kusumo (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Food security of a city will increase if its food availability is fulfilled. One way to optimize food security is by implementing urban farming as an alternative that can be applied to places with limited agricultural land, especially in cities filled with residential areas. In Bandung City, there is one farmer group that is actively developing urban farming, namely the Flamboyan Farmers Group. This research aims to describes the motivating factors for female members to be involved in urban farming and other public activities, analyze the role of female members in terms of the time they contribute, and analyze the amount of income they can contribute to their family income. The research method used a qualitative design with a case study technique. The results showed that the motivational factors that influence female members to be involved in urban farming activities and other public activities were internal factors based on their initiative. The time allocation contributed for urban farming activities is 42.44 % or as much as 33.5 hours / week. The average income contribution of female members from urban farming activies is 10.4 % to the total family income.